Sociocultural dimensions of lexis and text in the history of English - Petré, Peter (Linguist); Cuyckens, H.; D'Hoedt, Frauke (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2018)
The chapters collected in this volume examine how the sociohistorical and cultural context may influence structural features of lexis and text types. Each paper pays particular attention to social 'labels' and attitudes (conservative, religious, ideological, endearing, or other), thereby focusing on their dynamic and historical dimension. Changes in these are analyzed in order to explain morphological, lexical, and textual changes that would otherwise be hard to account for. Together, they provide a varied window on the effect of historical versions of a dynamic society on lexis and text. Examining lexical and textual change in history from a sociocultural perspective teaches us a great deal - not just about the past, but it also makes us think about similar phenomena in the present, enhancing our knowledge about how universally human some of these phenomena are.